2011
DOI: 10.1103/physrevc.83.014309
|View full text |Cite
|
Sign up to set email alerts
|

Structural evolution in Pt isotopes with the interacting boson model Hamiltonian derived from the Gogny energy density functional

Abstract: Spectroscopic calculations are carried out for the description of the shape/phase transition in Pt nuclei in terms of the interacting boson model (IBM) Hamiltonian derived from (constrained) Hartree-Fock-Bogoliubov (HFB) calculations with the finite range and density-dependent Gogny-D1S energy density functional. Assuming that the many-nucleon driven dynamics of nuclear surface deformation can be simulated by effective bosonic degrees of freedom, the Gogny-D1S potential energy surface (PES) with quadrupole deg… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
23
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(30 citation statements)
references
References 92 publications
6
23
1
Order By: Relevance
“…This feature appears to be independent of the choice of the EDF. A recent microscopic calculation using the Gogny-D1S EDF [13] also yielded shallow triaxial shapes, rather flat in the oblate region [37], but quantitatively consistent with the present analysis. A similar trend was reported in other EDF-based studies of ground-state shapes of Pt isotopes [39,48,49].…”
Section: Binding Energy Surfaces In the β-γ Planesupporting
confidence: 90%
See 1 more Smart Citation
“…This feature appears to be independent of the choice of the EDF. A recent microscopic calculation using the Gogny-D1S EDF [13] also yielded shallow triaxial shapes, rather flat in the oblate region [37], but quantitatively consistent with the present analysis. A similar trend was reported in other EDF-based studies of ground-state shapes of Pt isotopes [39,48,49].…”
Section: Binding Energy Surfaces In the β-γ Planesupporting
confidence: 90%
“…The corresponding IBM energy surfaces follow this evolution, but do not reproduce the triaxial minima because of the reasons explained above. The recent Gogny-EDF calculation [37] predicts 192 Pt to be the softest Pt isotope in this mass region.…”
Section: Binding Energy Surfaces In the β-γ Planementioning
confidence: 90%
“…A possible application would be to analyze neighboring isotopic chains, mercury, polonium, and platinum isotopes. In particular, the study in the platinum isotopes will help to disentangle if the single configuration is the appropriate picture to describe those isotopes (see, e.g., [19,43] and references therein). Other mass regions, including neutron-deficient krypton, selenium, and germanium isotopes and neutron-rich krypton, strontium, and zirconium isotopes, which are also known as regions of shape coexistence [4], would be a potential target.…”
Section: Discussionmentioning
confidence: 99%
“…By mapping the potential-energy surface (PES), obtained within the constrained self-consistent mean-field method with a given EDF, onto the expectation value of the corresponding IBM Hamiltonian, the energy spectra and electromagnetic transition rates have been computed. This method has been successfully applied to various shape phenomena, including vibrational and γ -unstable [41] as well as rotational deformed [42] nuclei, to prolate-oblate shape transitions [43], and to the study of the fingerprints of triaxiality [44].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the standard shell-model to boson-model mapping method [67,68], it has been shown that an IBM Hamiltonian can be determined, mapping a self-consistent mean-field total energy surface E(β,γ ) (over the full β-γ plane) onto the corresponding IBM mean-field energy. Very recently, this method was extended to include intruder mp-nh configurations, with a detailed coverage of the Pt, Pb, and Hg isotopes [69][70][71][72].…”
Section: Introductionmentioning
confidence: 99%